Demonstration of high-efficiency microwave heating producing record highly charged xenon ion beams with superconducting electron cyclotron resonance ion sources - X. Wang; J. B. Li; V. Mironov; J. W. Guo; X. Z. Zhang; O. Tarvainen; Y. C. Feng; L. X. Li; J. D. Ma; Z. H. Zhang; W. Lu; S. Bogomolov; et al. (Physical Review Accelerators and Beams, 2024)
Intense highly charged ion beam production is essential for high-power heavy ion accelerators. A novel movable Vlasov launcher for superconducting high charge state electron cyclotron resonance ion source has been devised that can affect the microwave power effectiveness by a factor of about 4 in terms of highly charged ion beam production. This approach based on a dedicated microwave launching system instead of the traditional coupling scheme has led to new insight on microwave-plasma interaction. With this new understanding, the world record highly charged xenon ion beam currents have been enhanced by up to a factor of 2, which could directly and significantly enhance the performance of heavy ion accelerators and provide many new research opportunities in nuclear physics, atomic physics, and other disciplines.